Highlighting multicomponent reactions as an efficient and facile alternative route in the chemical synthesis of organic-based molecules: a tremendous growth in the past 5 years - Mohlala, Reagan Lehlogonolo; Rashamuse, Thompho Jason; Coyanis, Elena Mabel (Frontiers in Chemistry, 2024)
Since Strecker’s discovery of multicomponent reactions (MCRs) in 1850, the strategy of applying an MCR approach has been in use for over a century. Due to their ability to quickly develop molecular diversity and structural complexity of interest, MCRs are considered an efficient approach in organic synthesis. Although MCRs such as the Ugi, Passerini, Biginelli, and Hantzsch reactions are widely studied, this review emphasizes the significance of selective MCRs to elegantly produce organic compounds of potential use in medicinal chemistry and industrial and material science applications, as well as the use of the MCR approach to sustainable methods. During synthesis, MCRs provide advantages such as atom economy, recyclable catalysts, moderate conditions, preventing waste, and avoiding solvent use. MCRs also reduce the number of sequential multiple reactions to one step.